2019
DOI: 10.1155/2019/5705126
|View full text |Cite
|
Sign up to set email alerts
|

Open‐Closed‐Loop PD Iterative Learning Control with a Variable Forgetting Factor for a Two‐Wheeled Self‐Balancing Mobile Robot

Abstract: A novel iterative learning control (ILC) algorithm for a two-wheeled self-balancing mobile robot with time-varying, nonlinear, and strong-coupling dynamics properties is presented to resolve the trajectory tracking problem in this research. A kinematics model and dynamic model of a two-wheeled self-balancing mobile robot are deduced in this paper, and the combination of an open-closed-loop PD-ILC law and a variable forgetting factor is presented. The open-closed-loop PD-ILC algorithm adopts current and past le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…In this section, an input disturbance observer (a proposal in [29]) is presented and applied for system (14). By using the Euler method, we have an approximate discrete-time model of system (14) as follows:…”
Section: Compound Disturbance Observermentioning
confidence: 99%
See 1 more Smart Citation
“…In this section, an input disturbance observer (a proposal in [29]) is presented and applied for system (14). By using the Euler method, we have an approximate discrete-time model of system (14) as follows:…”
Section: Compound Disturbance Observermentioning
confidence: 99%
“…eir nature is an unstable, underactuated, and nonlinear system, so it is very difficult to control them. ere have been many controllers designed for TWIRs such as backstepping [3,4], sliding mode control [5][6][7], nonlinear control [8][9][10][11], PID control [12,13], PD controller with iterative learning [14], fractional PID [15], fuzzy control [16,17], model predictive control [18], and nonlinear disturbance observer-based control [19].…”
Section: Introductionmentioning
confidence: 99%
“…However, they focused only on algorithm convergence, and an in-depth analysis of the forgetting factor effect on system output characteristics was not performed. In recent years, ILCs with forgetting factor, without enough supporting theory, have been applied to several engineering domains (Cao et al, 2015; Dong et al, 2019; Lan et al, 2017; Lin et al, 2019). Most reports indicated that the forgetting factor prevented the accumulation of initial resetting errors and interference.…”
Section: Introductionmentioning
confidence: 99%
“…Here, the feedback controller is directly incorporated in the learning scheme, by adding the control action to the learning signal. Several instances of these algorithms have been proposed over the years, as for example including integral actions [20], a time-variable forgetting factor [21], or its extension to networked systems [22].…”
Section: Introductionmentioning
confidence: 99%